Management support as a moderator in the HR practices employee performance relationship - Jibrin Bida, Mohammed; Abdul Majid, Abdul Halim; Ismail, AbdussalaamIyanda (Society of Scientific Research and Education (SSRE), 2017)
There seems an inconsistency in the findings regarding the HRM-performance relationship. While numerous HRM studies have signified positive effect of HR practices on employee performance, some other studies indicate the otherwise. Thus, this study investigates the effect of compensation, performance appraisal, and succession planning on employee performance. Through cross sectional survey approach, data were collected from 300 employees of state-owned Polytechnics in Nigeria. Partial Least Squares Method (PLS) algorithm and bootstrap techniques were used to test the study’s hypotheses. The results provided support for all the hypothesized relationships and signifying positive effect of compensation, performance appraisal, and succession planning on employee performance. This implies that effective HR practices (compensation, performance appraisal, and succession planning) enhance employee performance and thus organizations should entrench such HR practices in an effective manner. Besides, performance appraisal can impact performance of the employees if it is properly handled and laden with management support. Limitation and recommendations were also discussed.